Pengembangan Instrumen Kesepian Remaja: Analisis Model RASCH - Salsabila, Khansa; Yudha, Eka Sakti; Saripah, Ipah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
Loneliness is a common symptom that every individual can feel. Research on loneliness began to develop almost all over the world, especially during the COVID-19 pandemic. One of the main focuses is the development of loneliness instruments for instrument renewal. Participant; this instrument was tested on 683 high school students in Bandung. Result; analysis of the instrument using the RASCH model produces a Cronbach's alpha value of 0.77 which is in the excellent category, with item reliability of 0.99 in the particular category and personal reliability of 0.79, which is included in the excellent category. The conclusion is that this loneliness instrument can be used for further research.